COVID-19 in children treated with immunosuppressive medication for kidney diseases. Issue 8 (21st December 2020) - Marlais, Matko; Wlodkowski, Tanja; Al-Akash, Samhar; Ananin, Petr; Bandi, Varun Kumar; Baudouin, Veronique; Boyer, Olivia; Vásquez, Luciola; Govindan, Sukanya; Hooman, Nakysa; Ijaz, Iftikhar; Loza, Reyner; et al.
Abstract : Background: Children are recognised as at lower risk of severe COVID-19 compared with adults, but the impact of immunosuppression is yet to be determined. This study aims to describe the clinical course of COVID-19 in children with kidney disease taking immunosuppressive medication and to assess disease severity. Methods: Cross-sectional study hosted by the European Rare Kidney Disease Reference Network and supported by the European, Asian and International paediatric nephrology societies. Anonymised data were submitted online for any child (age <20 years) with COVID-19 taking immunosuppressive medication for a kidney condition. Study recruited for 16 weeks from 15 March 2020 to 05 July 2020. The primary outcome was severity of COVID-19. Results: 113 children were reported in this study from 30 different countries. Median age: 13 years (49% male). Main underlying reasons for immunosuppressive therapy: kidney transplant (47%), nephrotic syndrome (27%), systemic lupus erythematosus (10%). Immunosuppressive medications used include: glucocorticoids (76%), mycophenolate mofetil (MMF) (54%), tacrolimus/ciclosporine A (58%), rituximab/ofatumumab (11%). 78% required no respiratory support during COVID-19 illness, 5% required bi-level positive airway pressure or ventilation. Four children died; all deaths reported were from low-income countries with associated comorbidities. There was no significant difference in severity of COVID-19 based on gender, dialysis status, underlying kidney condition, and type or number of immunosuppressive medications. Conclusions: This global study shows most children with a kidney disease taking immunosuppressive medication have mild disease with SARS-CoV-2 infection. We therefore suggest that children on immunosuppressive therapy should not be more strictly isolated than children who are not on immunosuppressive therapy.